ANALISIS RISIKO PAJANAN TERHADAP PEKERJA KERAJINAN KAYU DI “ CV. X” KOTA PADANG - Nur, Erdi; Hidayanti, Rahmi; Yuliana, Rosi (HUMAN CARE JOURNAL, 2025)
Wood handicraft workers are informal sector workers who belong to the "underserved working population" and have not received maximum health services in an effort to minimize occupational diseases. The purpose of this study was to analyze the risk of dust exposure to woodworking workers at CV. X Padang City in 2020. This research is descriptive in nature by analyzing the risk of dust exposure of woodworking workers. The population is all workers in the production section (cutting/manufacturing and sanding and painting) totaling 18 people. The instruments in this study were the LVAS, thermohygrometer, anemometer, scales and checklists to observe activity patterns. Data analysis uses stages in environmental risk analysis. Respondents smoked while working is 62.5% and 66.7% use personal protective equipment. All pollutants are below the quality standard, while the results of the RQ (life time) value for all exposure materials are > 1 which means that the agent risk exposure is not safe after the employee has worked for 30 years. Management needs to carry out risk management such as reducing the concentration, time of exposure, and frequency of exposure to a safe limit by managing risk through technological approaches, socio-economic approaches, and institutional approaches